1970
DOI: 10.1002/chin.197018240
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: OXIDATIVE KUPPLUNG VON PHENOLEN 3. MITT. ISOLIERUNG UND KONSTITUTIONSBEWEIS EINES 8,6′‐VERKNUEPFTEN DEHYDRO‐DICATECHINS (B4)

Abstract: Bei der enzymatischen Dehydrierung von (+)‐Catechin (I) lassen sich Dehydro‐dicatechin A (10%), Dehydro‐dicatechin B1 ‐B4 (C30H26O12) (0,8; 0,2; 0,2 und 1,0%), die Isomere der Procyanidine der Gruppe B sind, sowie Dehydro‐tricatechin (0,2%) isolieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…This carbon resonance indicated that the two flavan-3-ol units were joined via an unusual C-2 f C-8′′ carbon-carbon linkage. The chemical shifts of C-6′′ (δ 109.65) and H-6′′ (δ 6.32) of 3 are similar to those in spectra of related ([2′,8]-and [6′,8]-) bis(+)-catechins coupled via their respective B-and A-rings (13,14). These assignments are supported by HMQC and HMBC spectral data.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…This carbon resonance indicated that the two flavan-3-ol units were joined via an unusual C-2 f C-8′′ carbon-carbon linkage. The chemical shifts of C-6′′ (δ 109.65) and H-6′′ (δ 6.32) of 3 are similar to those in spectra of related ([2′,8]-and [6′,8]-) bis(+)-catechins coupled via their respective B-and A-rings (13,14). These assignments are supported by HMQC and HMBC spectral data.…”
Section: Resultssupporting
confidence: 68%
“…HRP oxidation product 4 gave 611.1403, (M + H) + for C 30 H 27 O 14 , by HRFABMS indicating still another catechin dimer. The 1 H and 13 C NMR spectra of 4 were similar to those for 2. A meta-coupled B-ring with signals at δ 6.92 (d, J ) 1.0 Hz, H-2′) and 7.16 (d, J ) 1.0 Hz, H-6′) confirmed a (+)catechin B-ring coupling at C-5′ as in 2.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations